Electronic Structure of Above-Room-Temperature van der Waals Ferromagnet Fe3GaTe2 - Lee, Ji-Eun; Yan, Shaohua; Oh, Sehoon; Hwang, Jinwoong; Denlinger, Jonathan D.; Hwang, Choongyu; Lei, Hechang; Mo, Sung-Kwan; Park, Se Young; Ryu, Hyejin (American Chemical Society, 2023)
Fe3GaTe2, a recently discovered van der Waals ferromagnet, demonstrates intrinsic ferromagnetism above room temperature, necessitating a comprehensive investigation of the microscopic origins of its high Curie temperature (T-C). In this study, we reveal the electronic structure of Fe3GaTe2 in its ferromagnetic ground state using angle-resolved photoemission spectroscopy and density functional theory calculations. Our results establish a consistent correspondence between the measured band structure and theoretical calculations, underscoring the significant contributions of the Heisenberg exchange interaction (J(ex)) and magnetic anisotropy energy to the development of the high-T-C ferromagnetic ordering in Fe3GaTe2. Intriguingly, we observe substantial modifications to these crucial driving factors through doping, which we attribute to alterations in multiple spin-splitting bands near the Fermi level. These findings provide valuable insights into the underlying electronic structure and its correlation with the emergence of high-T-C ferromagnetic ordering in Fe3GaTe2